Seroprevalence of anti HCV antibodies among blood donors: a retrospective study from Haryana, India - Sehgal, P. K.; Garg, Anubha (International Journal of Research in Medical Sciences, 2017)
Background: HCV is known for its chronicity and leads to cirrhosis in about 10 to 20 per cent of patients and may further progress to hepatocellular carcinoma (HCC). The global seroprevalence of HCV among blood donors varies from 0.4 to 19.2 per cent and the estimated risk for HCV transmission is between 0.10 to 2.33 per million units transfused. ELISA is the most commonly used initial assay for detecting HCV antibodies. The purpose of the present analysis was to monitor the seroprevalence of anti-HCV antibodies in the blood donor population in a hospital based blood bank in north India for a period of 10 years (2007-2016), and to evaluate the trends over the years. Methods: The purpose of the present analysis was to monitor the seroprevalence of anti-HCV antibodies in the blood donor population in a hospital based blood bank in north India for a period of 10 years (2007-2016), and to evaluate the trends over the years. Results: Of the total 340078, 298421 (87.75%) collections were voluntary and 41657 (12.25%) were replacement collections. A prevalence of 0.72% of hepatitis C virus infection was seen among the donors from the period 2007-2016. The trend of hepatitis C prevalence among donors has been fluctuating while ranging from 0.51% to 0.89%. Conclusions: For a safe blood service in our country, where comprehensive laboratory tests are neither possible nor pragmatic, it is best to switch over to 100% voluntary donations, as it is now established that only voluntary non-remunerated regular donation is the safest. Thus, one of our key strategies to enhance blood safety is to focus on motivating non-remunerated blood donors and phasing out even replacement donors. Since, no vaccine is presently available for immunization against HCV infection, transfusion transmitted HCV infection remains a potential threat to the safety of the blood supply.